Medical management of paediatric burn injuries: Best practice part 2. Issue 9 (3rd April 2013) - D'Cruz, Rachel; Martin, Hugh CO; Holland, Andrew JA
Abstract : Burns remain a leading cause of injury in the paediatric population in Australia despite efforts in prevention. Advances in surgical management include novel debridement methods and blood conserving techniques. Patients with severe burns (>20%) remain significantly more complex to manage as a result of extensive alterations in metabolic processes. There appears increasing evidence to support the use of pharmacological modulators of the hyper‐metabolic state in these patients. The management of a child with burns involves acute, subacute and long‐term planning. This holistic approach seems optimally co‐ordinated by a Burns Unit in which each discipline required to provide care to these children in order to achieve optimal outcomes is represented.